Andrographis nallamalayana, a heterotypic synonym of a little-known endemic species A. beddomei (Acanthaceae) - Gnanasekaran, G.; Rajakullayiswamy, K.; Murthy, G. V. S. (Rheedea, 2015)
Andrographis nallamalayana J.L. Ellis, a well-known endemic species from the Eastern Ghats of Andhra Pradesh, is reduced here to a synonym of a little-known endemic species, A. beddomei C.B. Clarke. A detailed description, photographs, and distribution map of the species are provided here.